THE ANALYZE OF FIGURATIVE LANGUAGE OF THE DOEL SUMBANG'S SONG LYRIC "BULAN BATU HIU" - Muhammad Wildan Hakim; Nenden Rikma Dewi (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2021)
Figurative language is used to express feelings by using particular style and dictions. It exist in various way, but it can be identified clearly in literary works and songs. Doel Sumbangâ€™s â€œBulan Batu Hiuâ€, for example, contains various type of figurative language. Thus, this research is aimed to find out the types of figurative language and meanings of figurative language in the Doel Sumbangâ€™s song Lyric â€œBulan Batu Hiuâ€. The methodology of this research is qualitative research. Data are taken from the lyric song. To analyze the issue, this research is using Knickerbocker and Williard Reninger (1963) ideas on classification of figurative language. As the result, Doel Sumbangâ€™s song Lyric â€œBulan Batu Hiuâ€ has two types of figurative language, personofocations and hyperboles. There are three personifications and three hyperboles types which describe connotative meaning.